Integration of Energy Service Components into an Open System for Future Energy Markets - Gervais Usha McKoy and Ervin Victor Madaha (2018)
De-centralized renewable energy generation in houses and farms together with their local consumers and a local energy management system (typically a household control box) can act as prosumers already nowadays. The project OS4ES (Open System for Energy Services) provides a registry-based ICT infrastructure that supports the offering and aggregation of local flexibility to larger energy amounts that the aggregator can trade on energy markets. In future smart grids the registry will act as a market plattform where prosumers can offer their energy services to get booked by the aggregators. The objective of this work was a lab test where real physical devices offer their flexibility to the registry and get operated by an aggregator instance that has booked that flexibility from the registry. A testbed for the prototypical implementation of the OS4ES has been designed and implemented in order to prepare that lab test. Finally the lab test was executed with a simulated PV-battery system and with a real CHP (Combined Heat and Power) in the Smart Grid Lab of the CC4E in the Energy Campus Bergedorf.